Proceedings of the 2020 ACM/IEEE Workshop on Machine Learning for CAD 2020
DOI: 10.1145/3380446.3430629
|View full text |Cite
|
Sign up to set email alerts
|

Track-Assignment Detailed Routing Using Attention-based Policy Model With Supervision

Abstract: Detailed routing is one of the most critical steps in analog circuit design. Complete routing has become increasingly more challenging in advanced node analog circuits, making advances in efficient automatic routers ever more necessary. In this work, we propose a machine learning driven method for solving the track-assignment detailed routing problem for advanced node analog circuits. Our approach adopts an attention-based reinforcement learning (RL) policy model. Our main insight and advancement over this RL … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The algorithm is designed to encode the design rules into the track-assignment steps, and the model determines the best sequence of the set of device pairs to be routed, such that the overall solution quality is maximized. In [168], the training of the reinforced learning model was supervised with past solutions, leveraging the information previously produced. Both methods provide nearly 100× runtime speed-ups when comparing with a plain schedular based on an EA, while generating solutions that are comparable in quality.…”
Section: Assisted By Machine/deep Learningmentioning
confidence: 99%
“…The algorithm is designed to encode the design rules into the track-assignment steps, and the model determines the best sequence of the set of device pairs to be routed, such that the overall solution quality is maximized. In [168], the training of the reinforced learning model was supervised with past solutions, leveraging the information previously produced. Both methods provide nearly 100× runtime speed-ups when comparing with a plain schedular based on an EA, while generating solutions that are comparable in quality.…”
Section: Assisted By Machine/deep Learningmentioning
confidence: 99%
“…Recent years, deep learning based EDA routing method has been widely concerned by the industrial and academic community. For integrated circuits (IC) routing, some deep reinforcement learning methods have been presented for global routing (Liao et al 2020b), detail routing (Lin et al 2021c), and track assignment (Liao et al 2020a). Deep reinforcement learning has also been shown to solve some fundamental problems, including rectilinear Steiner minimum tree problem (Liu, Chen, and Young 2021) and travelling salesman problem (Kool, Van Hoof, and Welling 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Probability calculations using h (c) , and h i , i ∈ {1, ..., N × M } in (11)(12)(13)(14) are exactly identical to (5)(6)(7)(8) in [19] except the masking mechanism in equation 13 and equation 14. Because [19] solves TSP, so they mask the previously selected actions by forcing −∞ as compatibility u (c)j .…”
Section: D3 Calculation Of Probabilitymentioning
confidence: 99%
“…Many studies have already shown that deep reinforcement learning (DRL), one of the representative ML method for sequential decision making, is applicable to various tasks in modern chip design; chip placement [2,3], routing [4,5], circuit design [6], logic synthesis [7,8] and bi-level hardware optimization [9]. However, most DRL-based hardware design methods used simplified objectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation